External Sources Inhibit Benthic Phosphorus Fluxes in the Lower Great Miami River, Southwest Ohio. (12th June 2020) - Mullen, Kortney R.; Hammerschmidt, Chad R.; Ekberg, Michael P.; McCarthy, Mark J.; Newell, Silvia E.; Agather, Alison M.
Abstract: Human activities have increased nutrient loadings to aquatic ecosystems, especially during the past century. During low river flow in late summer and early fall, elevated concentrations of phosphorus (P) and nitrogen are present in the temperate Lower Great Miami River and contribute to its eutrophication. Although wastewater treatment plants are suspected of being major sources of P to the river, riverbed sediment has not been examined as an additional potential source of P. Benthic P fluxes were measured at 11 representative locations along the Lower Great Miami River during 3 sampling campaigns in late summer and early fall of 2015. Benthic fluxes of filtered total P (range, −1.6−12 mg m −2  d −1 ) were related inversely to filtered total P concentrations in river water ( p  = 0.002, r  = −0.60). This relationship suggests that elevated P in river water inhibits mobilization from sediment, likely by minimizing the concentration gradient between porewater and overlying water. To effectively mitigate long‐term effects of legacy P stored in Lower Great Miami River sediments, external sources must continue to be managed and discharges reduced to allow legacy P to be mobilized and flushed from the system. Reducing nutrient loading will help protect water quality in the Lower Great Miami River, in other comparable rivers, and in downstream aquatic habitats. Environ Toxicol Chem 2020;39:1517–1525. © 2020 SETAC